Digital Financial Literacy for MSMEs: The Role of QRIS, GoPay, and BukuKas in Tonja Village - I Wayan Dikse Pancane; I Gusti Ayu Wirati Adriati (GUYUB: Journal of Community Engagement, 2025)
In the contemporary digital era, the utilization of technology, particularly digital financial applications, has become imperative for Usaha Mikro, Kecil, dan Menengah  (MSMES) to enhance efficiency and transparency in business financial management. Nevertheless, a considerable impediment persists in the form of inadequate digital financial literacy, a predicament that is particularly pronounced in rural regions such as Tonja Village. This community service activity aims to enhance the understanding and proficiency of MSMES actors in utilizing digital financial applications through an educational approach leveraging social media. The method employed involves the creation and dissemination of visually appealing and informative educational posters via the Instagram platform, ensuring easy access for MSMES players at any time. This strategy was selected to reach a broader audience and align with the information consumption patterns of the contemporary digital society. The evaluation of this initiative revealed a substantial enhancement in the comprehension and enthusiasm of MSMES participants concerning the utilization of digital financial applications for the management of business finances. It is anticipated that this initiative will lead to a lasting enhancement in digital financial literacy, empowering MSMES players in Tonja Village to manage their finances with greater organization, efficiency, and accountability, thereby fostering their business growth.